THE EFFECTIVENESS OF LKPD IPA BASED ON SCIENCE PROCESS SKILLS TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS ON SINGLE SUBSTANCE AND MIXED SUBSTANCES MATERIAL - Nora Deselia Saragih; Nurdin Bukit; Sriadhi Sriadhi (Jurnal Ilmiah Teunuleh, 2022)
The purpose of this study is to determine the feasibility and effectiveness of developing worksheets for science students based on contextual teaching and learning (CTL) to improve critical thinking skills. This research is based on development research, with a sample of grade V students of Binjai Methodist Private Elementary School. Data analysis techniques use descriptive studies and t-tests. The results of the research and conclusions in this study are: 1) For the feasibility test in this development research, namely the results of expert validation tests conducted on 3 experts, namely Indonesian experts, material experts and learning media experts. Obtained an expert score of Indonesian of 35 with a percentage of 72.92% (quite valid), then a score by a material expert obtained 55 with a percentage of 85.94% (Valid). Then the score by the learning media expert was 64 with a percentage of 69.75% (quite valid). The results of the field trial in this study obtained the number of scores from 28 students, the average score obtained was 49.07 with a percentage of 87.63% (Valid). For the effectiveness test, from the results of the calculation of the data obtained thitung = 8.34 from the distribution list t using the odds of 1-? = 0.95 with dk n-1 (27-1) = 26, obtained the price of ttabel = 4.25. So that a calculation of > ttable was obtained, with the hypothesis stated "There is an effectiveness of a Contextual Teaching and Learning (CTL) Based Science Student Worksheet on the material "single substance and mixed substance" in Class V of Binjai Methodist Private Elementary School"